Who owns the sky? Aerial resistance and the state/corporate no-fly zone. Issue 5 (19th October 2020) - Keysar, Hagit
Abstract : "Who owns the sky" is not a new question but a persistent one. For more than three centuries it emerges as a social, legal, technological, and geopolitical problem. Indeed, the aerial is not something that is simply above our heads but an element that fluctuates in and out of the body. And while the air and the body are inseparable, the aerial has been turned directly against the body in various ways since the beginning of the 20 th century. This paper explores the unsettled frontiers of the fly-zone, looking into the interrelated occupations, exploitations, and democratizations of the aerial. It sketches the emergence of the state/corporate no-fly zone (NFZ) through the emergence of small-scale civilian drones, which developed into a sophisticated industry that negotiates new forms of state power to technology corporations. This new configuration of aerial control and management complicates the established, state-imposed, regulatory NFZ and suggests the development of a new techno-cultural assemblage of spatial closures through the air. Against this backdrop, I discuss two case-studies of aerial resistance through the use of do-it-yourself (DIY) aerial-photography in Israel/Palestine. I show how DIY tactics and tools offer a distinctive kind of evocation and provocation that challenge the conceptual and material boundaries of the NFZ and direct the attention to the ruptured links between the aerial and the human body. Finally, I discuss how DIY aerial-photography is also a particular kind of testimony and a methodological mediation that allows questioning the very premise of knowledge production through technosocial, activist engagement.